Pharmacological Benefits Extracts of Putri Malu (Mimosa pudica Linn.) in Herbal Medicine: A Review - Ananda, Meisya Dwi; Mierza, Vriezka; Khaerunisa, Aulia; Apriani, Risa Dwi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Herbal medicine has a long history of use as an alternative therapy, especially for acute and chronic diseases. There have been many studies on the Putri Malu plant (Mimosa pudica Linn.) to uncover its pharmacological activities. This review paper aims to examine the secondary metabolites present in the extracts of the plant putri malu (Mimosa pudica Linn.) and their potential pharmacological actions. The method used was a Systematic Literature Review (SLR), which collected publications from PubMed, ScienceDirect, and Google Scholar databases. From this process, 15 studies were identified that met the predetermined inclusion criteria. Most of the studies used extracts of the leaves putri malu (Mimosa pudica Linn.) with ethanol solvent as the leading choice for extraction. The pharmacological activities found include antioxidant (20%), anti-inflammatory, anticancer, and antidiabetic (13.3% each) and contain antibacterial, anticonvulsant, antihelminthic, diuretic, hepatoprotective, antimalarial, antidepressant, and antihyperlipidemic (6.7% each). In conclusion, extracts of the plant putri malu (Mimosa pudica Linn.) show great potential for use in herbal medicine. Its wide range of pharmacological actions backs its advantages in treating and preventing several illnesses.